Simulation on modified hysteresis current control in half-bridge bidirectional DC-DC converter - Nurul Azwa, Othman; Hamdan, Daniyal; Mohd. Shafie, Bakar (Asian Research Publishing Network (ARPN), 2015)
This paper proposes a modified hysteresis current control method for half bridge bidirectional DC-DC converter (HBDC). Hysteresis current controller is modified by adding logic circuit at input signal S1 and S2 to change performance of inductor current, IL. According to current direction transition, IL stays at zero in a moment. It is happens when Irefp is crossing zero and continues bouncing when Irefm is crossing zero. This method is applied to reduce loss in HBDC performance, which as a result will achieve reduction in switching losses and conduction losses. The conduction losses and switching losses has been analyzed which conduction losses has slight changes in losses reduction and switching losses is reduce from 6.31 J to 4.53 J. The proposed hysteresis current controller was simulated using PSIM and the losses is verify on each switching changes. The result validated proposed hysteresis current control capability in losses reduction.